A mistletoe marriage reunion - Heaton, Louisa (Harlequin medical romance, 2024)
Once her children left home, Lauren could finally pursue her surgical dreams. Sadly, her marriage to surgeon Oliver didn’t survive the different directions life took them… A decade later, she’s back in London and face-to-face with her ex-husband—who’s annoyingly more gorgeous than ever! Oliver understands why they fell apart, so he’s surprised at the attraction still sizzling between them… Soon they’re reconnecting over hot chocolates and even hotter mistletoe kisses! Dating again is fun, but with their history, can they risk taking things any further?